Extension of Time (EoT) Considerations in Construction Duration Estimate for Public Construction Projects - S. N., Ting; V. C., Darrell; A. B. H., Kueh; Y. Y., Lee; C.K., Ng (IOP Publishing, 2021)
Construction duration is defined as the time frame given by the Client of a project use to complete the project under normal working conditions, practice of construction. However, often times, projects faced time overruns and hence, needing to activate contractual remedies like Extension of Time (EoT). This paper aims to investigate the factors related to award the Extension of Time (EoT) for construction projects in especially in the public sector in Sarawak. A structured checklist was created as an instrument and employed to accomplish the objective of this research. A total of 111 previous public projects which were granted EoT were studied. The findings revealed several detailed factors that had typically led to project delays in the State. These findings are expected to offer the construction industry stakeholders in Sarawak a focal point on those delay that could be included in construction project duration estimates and management of construction performances, followed by the appropriate corrective and improvement measures for time management for construction projects.